Criminal Liability for Environmental Pollution in Indonesian Law - Hasudungan Sinaga (Pelopor Publikasi Akademika, 2023)
This research aims to delve into criminal liability in the context of environmental pollution offenses within the criminal law domain in Indonesia. Through a normative legal research approach with an analysis of legislation regulating environmental pollution, this study identifies and specifically examines the juridical regulations related to environmental pollution offenses. The research findings affirm that the legal foundation for environmental pollution offenses in Indonesia is governed by Law No. 32 of 2009 concerning Environmental Protection and Management. Additionally, this study highlights criminal liability that can be imposed on various parties, including individuals, businesses, and officials with relevant authority. Furthermore, the research suggests that the application of law regarding environmental pollution offenses is generally found in various legal regulations governing aspects of environmental protection and management. In addition to individuals, businesses, or corporations can also be held accountable for environmental pollution offenses, as stipulated in Articles 116-118 of Law No. 32 of 2009. Taking these aspects into consideration, this research makes a significant contribution to understanding and solidifying the legal framework governing criminal liability related to environmental pollution offenses in Indonesia. This provides a strong foundation to promote awareness and compliance with environmental laws, as well as to protect the sustainability of the environment for the well-being of society and future generations